Perancangan Sistem Chick Maintenance Cycle Menggunakan ERP Pada PT Charoen Pockphand - Liana, Laurensia; Supriana, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2019)
The development of the world of computers and information technology has been very rapid in recent years. A company needs an information system that can accommodate various needs of the company in carrying out business processes. With the application of information systems to companies, business processes can run more smoothly and faster. PT. Charoen Pockphand Indonesia wants to create a new system based on an existing system using an ERP or Enterprises Planning Resource. ERP was chosen because it has a wide operating area of functionality, namely Marketing and Sales, Supply Chain Management, Accounts and Finance, and Human Resources.